An Analysis of English Department Students’ Skill in Writing Argumentative Essay in FKIP UNES Padang - Desi Nopita Sari; Widya Juli Astira; Lailatul Husna (Kilau Publishing, 2026)
The objective of this research was to find out the students’ skill and students' difficulties in writing argumentative essay. This research has been done on English Department students’ FKIP UNES Padang in the 2023/2024 academic years. The students’ had five problems, there were difficult to investigate a topic, difficult in organizing idea, lack of vocabulary, not understand the language features, and lack of mechanic. The method used in this study was quantitative research. The researcher found that the students' skill in English Department writing argumentative essay for four semester good category. It was indicated by the scientific fact that 2 students from 14 students had excellent category with a percentage (14.28%), 5 students from 14 students had very good category with a percentage (28,57%), there are 6 students from 14 students had good category with a percentage (50%), the next 1 students get fair category with a percentage (7%) and the poor category is not found by all the students. The researcher concluded that students writing skill in argumentative essay was 62% very good category.